Calculus of variations with fractional derivatives and fractional integrals - Almeida, R.
We prove the Euler-Lagrange fractional equations and the sufficient optimality conditions for problems of the calculus of variations with functionals containing both fractional derivatives and fractional integrals in the sense of Riemann-Liouville. © 2009 Elsevier Ltd. All rights reserved.